Job Search and Frictional Unemployment : Some Empirical Evidence - Bruce, C.; Marshall, J. (Relations industrielles / Industrial Relations, 1976)
The purpose of this paper is to report on some recent empirical research undertaken in order to provide additional information concerning the frictionally unemployed.